Jesus e a solidariedade com os excluídos - Benincá, Dirceu (Revista Eclesiástica Brasileira, 2007)
O presente texto, de caráter pastoral, se insere na perspectiva apontada pelo 11º encontro intereclesial de CEBs (19 a 23 de julho de 2005), em Ipatinga – MG, que enfoca a espiritualidade libertadora, com o tema “Seguir Jesus no compromisso com os excluídos”. Associa-se também à proposta da CNBB com o atual Projeto Nacional de Evangelização (20042007) que tem como tema: “Queremos ver Jesus – Caminho, Verdade e Vida”. Em linguagem popular, desejamos reafirmar a prática histórica de Jesus como ponto de partida fundamental para compreender o projeto do Reino de Deus e torná-lo possível entre nós. Abstract: The present text, of a pastoral nature, is inserted into the perspective pointed by the 11th Inter-ecclesial meeting of the Ecclesiastical Grassroots Communities (CEBs) held between 19th and 23rd July 2005 in Ipatinga, Minas Gerais. The meeting focused on a liberating spirituality with the theme “To follow Jesus in our commitment to help the excluded”. It is also associated with the CNBB (National Conference of the Brazilian Bishops) in the present National Project of Evangelization (2004-2007) that also has as its main theme: “We want to see Jesus – Way, Truth and Life”. In a simple language we wish to reaffirm Jesus’historical praxis as an essential starting point for the understanding of the project of God’s Kingdom and as a way to make it possible in our midst.